Analisis Kinerja Pemerintah Daerah dengan Rasio Keuangan - Ardi, Pahmi; Junaidi; Akmadani, Oggy (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the performance of local governments using financial ratios from an agency theory perspective. The research method used is quantitative descriptive. The data collection technique is documentation using secondary data, namely the budgeting realitation report and the Bengkayang Regency Government Balance Sheet Report. The analysis techniques used include the current ratio, debt-to-equity ratio, PAD growth ratio, regional autonomy ratio, DCSR, and WCTA, which are further analyzed using agency theory. The overall current ratio calculations show good values, with values exceeding 5 from 2019 to 2021. However, the current ratio decreased in 2022–2023. The debt-to-equity ratio overall shows positive values, with significant increases from 2019 to 2022, followed by a decrease of 0.098 in 2023. The PAD growth ratio in 2019-2022 shows a significant increase in positive performance by the government, but there was a 2% decline in 2023, which must be explained transparently by the government to avoid information asymmetry. The independence ratio in 2019-2023 shows an instructive pattern, explaining the government's high dependence on transfer funds. The DCSR for 2019-2021 was above the 2.5 threshold, while in 2022 the DCSR value was below the threshold, necessitating anticipation of the risk of inability to pay debts. However, this was improved with an increase in the DCSR value in 2023 above the threshold. WCTA experienced a significant increase from 2019 to 2021, but from 2022 to 2023, WCTA decreased to 0.023 (2022) and 0.006 (2023), indicating limited working capital.